Elucidating the Dubai boutique and its consumer - Venter, Kerry/ KL (2016)
This paper considers the potential of the boutique in Dubai, UAE whilst associated research seeks to elucidate the internal and external drivers that will motivate a consumers’ decision-making process in a Dubai boutiques favour. Utilzing qualitative and quantitative research methods numerous internal and external variables of influence on the Dubai boutique consumers decision-making process were revealed. Although research results are not generalizable to the entire population of Dubai boutique consumers they serve as a valuable resource for future research. This is of importance considering the gap in research available regarding Dubai boutiques and Dubai boutique consumer behavior; and considering the gap in the market of Dubai for boutique accommodation.